Childhood Epilepsy; Prognostic Factors in Predicting the Treatment Failure - TAGHDIRI, Mohammad Mehdi; OMIDBEIGI, Mahmoud; ASAADI, Sina; GHOFRANI, Mohammad (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Taghdiri MM, Omidbeigi M, Asaadi S, Mohebbi M, Azarghashb E, Ghofrani M. Childhood Epilepsy; Prognostic Factors in Predicting the Treatment Failure. Iran J Child Neurol. Winter 2017; 11(1):21-28. Abstract Objective We aimed to find the prognostic factors to detect the patients who fail the treatment of epilepsy, in the early stages of the disease. Materials & Methods This study was done on the epileptic patients attending the Neurology Clinic of Mofid Children’s Hospital, Tehran, Iran from September 2013 to October 2014. After defining the criteria for exclusion and inclusion, the patients were divided to two groups based on responding to the medical treatment for their epilepsy and indices were recorded for all the patients to be used in the statistical analyses. Results The patients’ age ranged from 1 to 15 yr. There was 188 patients with refractory seizure in group 1 (experimental group) and 178 patient with well controlled seizure in group 2(control group).There was a significant different between serum drug level in both groups and patients with refractory seizure group had a lower serum drug level than control group. In both groups tonic-clonic was the most common type of seizure. Also the prevalence of brain imaging Abnormalityand other neurologic disorders was significantly higher in patients with refractory seizure in compare with control group. Conclusion Children with seizure who suffer from refractory epilepsy need more attention and exact observation by the medical staff. References 1. Kozyrskyj AL, Prasad AN. The burden of seizures in Manitoba children: a population-based study. Can J Neurol Sci 2004;31:48-52. 2. Camfield PR, Camfield CS, Gordon Kandet al. If a first antiepileptic drug fails to control a child’s epilepsy, what are the chances of success with the next drug? J Pediatr 1997; 131:821-4. 3. Arts WF, Brouwer OF, Peters ACet al. Course and prognosis of childhood epilepsy: 5-year follow-up of the Dutch study of epilepsy in childhood. Brain 2004;127:1774–84. 4. Berg AT, Shinnar S, Levy SR, et al. Early Development of intractable epilepsy in children: a prospective study. Neurology 2001;56:1445–52. 5. Berg AT, Vickrey BG, Testa FM, et al. How long does it take for epilepsy to become intractable? A prospective investigation. Ann Neurol 2006;60:73–9. 6. Kwan P, Brodie M. Early identification of refractory epilepsy. N Eng J Med2000;342:314–9. 7. Mohanraj R, Brodie MJ. Diagnosing refractory epilepsy: response to sequential treatment schedules. Eur J Neurol 2006;13:277–82. 8. Berg A. Identification of Pharmacoresistant Epilepsy. Neurol Clin 2009;27(4):1003-1013. 9. Luciano AL, Shorvon SD. Results of treatment changes in patients with apparently drug-resistant chronic epilepsy. Ann Neurol 2007;62:375–381. 10. Carpay HA, Arts WF, GeertsAT, et al. Epilepsy in childhood: An audit of clinical practice. Arch Neurol 1998;55:668–73. 11. Dudley RW, Penney SJ, Buckley DJ. First-drug treatment failures in children newly diagnosed with epilepsy. Pediatr Neurol 2009;40:71–7. 12. Berg AT, Vickrey BG, Testa FM, et al. How long does it take epilepsy to become intractable? A prospective investigation. Ann Neurol 2006;60:73–79. 13. Spooner CG, Berkovic SF, Mitchell LA, et al. New onset temporal lobe epilepsy in children: lesion on MRI predicts poor seizure outcome. Neurology 2006;67:2147–2153. 14. Robinson RO, Baird G, Robinson Get al. Landau– Kleffner syndrome: course and correlates with outcome. Dev Med Child Neurol2001;43:243-7. 15. Berg AT, Shinnar S, Levy SR, et al. Defining early seizure outcomesin pediatric epilepsy: the good, the bad and the in-between. Epilepsy Res 2001;43:75-84. 16. Shinnar S, Berg AT. Does antiepileptic drug therapy prevent the development of ‘‘chronic’’ epilepsy? Epilepsia 1996;37:701-8.Neurol Clin 2009;27(4):1003-1013. 17. Engel J. The goal of epilepsy therapy: no seizures, no side effects,as soon as possible. CNS Spectrums 2004;9:95–97. 18. Mathern GW, Pretorius JK, Babb TL. Influence of the type ofinitial precipitating injury and at what age it occurs on courseand outcome in patients with temporal lobe seizures. J Neurosurg1995;82:220 –227. 19. Cross JH, Jaykar P, Nordli D and et al. Propose criteria for referraland evaluation of children for epilepsy surgery: recommendations of the Subcomission for Pediatric Epilepsy Surgery. Epilepsia2006;47:953–959. 20. Weiner HL, Carlson C, Ridgway EBet al. Epilepsy surgery inyoung children with tuberous sclerosis: results of a novel approach. Pediatrics 2006;117:1494 –1502. 21. Del Felice A, Beghi E, Boero G, La Neve A, Bogliun G, De Palo A, et al. Early versus late remission in a cohort of patients with newly diagnosed epilepsy. Epilepsia 2010;51(1):37-42. 22. Levy SR, Novotny EJ, Shinnar S. Predictors of intractable epilepsy in childhood: a case–control study. Epilepsia 1996;37:24–30. 23. Berg AT, Shinnar S, Levy SR and et al. Smith- Rappaport S, Beckerman B. Early development of intractable epilepsy in children: a prospective study. Neurology2001;56:1445–52. 24. Casetta I, Granieri E, Monetti VC et al. Early predictors of intractability in childhood epilepsy: a community-based case–control study in Copparo, Italy. Acta Neurologica Scandinavica 1999;99:329–33. 25. Chawla S, Aneja S, Kashyap Ret al. Etiology and clinical predictors ofintractable epilepsy. Pediatric Neurology 2002;27:186–91. 26. Ko TS, Holmes GL. EEG and clinical predictors of medically intractable childhood epilepsy. Clin Neurophysiol 1999;110:1245–51. 27. Kwong KL, Sung WY, Wong SN, et al. Early predictors of medical intractability in childhood epilepsy. Pediatr Neurol2003;29:46–52. 28. Oskoui M, Webster RI, Zhang X and et al. Factors predictive of outcome inchildhood epilepsy. J Child Neurol 2005;20:898–904. 29. Seker Yilmaz B, Okuyaz C, Komur M. Predictors of Intractable Childhood Epilepsy. Pediatr Neurol 2013;48(1):52-55. 30. Kim S, Park K, Kim S, Kwon O, No S. Presence of epileptiform discharges on initial EEGs are associated with failure of retention on first antiepileptic drug in newly diagnosed cryptogenic partial epilepsy: A 2-year observational study. Seizure 2010;19(9):536-539. 31. Callaghan B, Anand K, Hesdorffer D, Hauser W, French J. Likelihood of seizure remission in an adult population with refractory epilepsy. Ann Neurol 2007;62(4):382- 389. 32. Arhan E, Serdaroglu A, Kurt A, Aslanyavrusu M. Drug treatment failures and effectivity in children with newly diagnosed epilepsy. Seizure 2010;19(9):553-557.